1994
DOI: 10.1037/0022-3514.67.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality of observer ratings on the California Adult Q-set.

Abstract: The dimensionality of personality ratings on the California Adult Q-set (CAQ) is examined in a sample of 940 subjects. Solutions of between 5 and 15 factors are examined; interrater agreement is assessed for items, factors, and items partialing factors. Results suggest that the 5 personality factors are important yet not exhaustive in accounting for common factor variance in the CAQ. Furthermore, interjudge agreement extends beyond the 5 dimensions. Likely explanations for these results are considered, and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 43 publications
0
47
0
Order By: Relevance
“…They found three additional factors: Attractiveness, Insight, and Ambition. Lanning (1994) also obtained these three additional factors when factor-analysing CAQ ratings. These studies provide clear evidence that Gough's CPI scales and the CAQ are measuring constructs that are missing from the Five Factor Model.…”
Section: Criticisms Of the Five Factor Modelmentioning
confidence: 98%
“…They found three additional factors: Attractiveness, Insight, and Ambition. Lanning (1994) also obtained these three additional factors when factor-analysing CAQ ratings. These studies provide clear evidence that Gough's CPI scales and the CAQ are measuring constructs that are missing from the Five Factor Model.…”
Section: Criticisms Of the Five Factor Modelmentioning
confidence: 98%
“…In that case, he should be most interested in the results of a study by Lanning (1994). Lanning analyzed data from the Institute of Personality and Social Research.…”
Section: Uncited Empirical Evidencementioning
confidence: 98%
“…Analyses of some of the first administration data in the BLSA (McCrae, Costa, & Busch, 1986) showed that the CAQ included items from all five factors of the FFM, and that a five-factor structure captured most of the common variance in CAQ items (cf. Lanning, 1994). Five varimax-rotated factors were extracted from the intercorrelation of the CAQ items on both occasions, yielding the expected N, E, O, A, and C factors.…”
Section: Methodsmentioning
confidence: 99%